CONSUMER PROTECTION IN BEACH TOURISM OBJECTS FROM THE PERSPECTIVE OF MAQASHID SHARIA (STUDY IN THE SUB-DISTRICT OF MIRROR BEACH, SERDANG BEDAGAI DISTRICT) - Trihafsari, Wiwik; Permata, Cahaya (Universitas Islam Negeri Mataram, 2024)
Activities in tourist attractions pose a risk of danger for tourists, which can impact safety and security, including beach tourism. It must be backed by infrastructure that promotes safety and security in these tourist locations to reduce current risks. Visitors' rights to safety, security, and clear information are guaranteed by Law No. 8 of 1999 on consumer protection and Law No. 10 of 2009 on tourism, specifically Article 20. This study aims to investigate how the Pantai Cermin District's beach attractions' facilities, their consumer protection policies, and the notion of consumer protection as seen through the lens of Maqashid Sharia. This study employs a conceptual framework, a statute-based methodology, and an empirical case-study approach to the law. The results of this study indicate that the facilities at beach attractions in Pantai Cermin Subdistrict still need to fulfil safety and security aspects, such as the unavailability of health clinics, watchtowers, and luggage storage for tourists. In the perspective of maqashid sharia, consumer protection of security and safety in beach tourism is the application of the principles of Hifz al-Nafs (protecting the soul) and Hifz al-Mal (protecting property), so beach tourism managers must provide security, health, and safety facilities for beach visitors.